Public television in the digital era : technological challenges and new strategies for Europe - Iosifidis, Petros (Palgrave Macmillan, 2012)
By looking at a range of different European Public Television (PTV) broadcasters, this book investigates the challenges that these broadcasters encounter in a competitive digital broadcasting environment and reveals the different policies and strategies they are adopting in order to remain accountable, competitive and efficient